The Security Gap in Syria: Individual and Collective Security in 'Rebel-held' Territories. Issue 1 (16th July 2015) - Ali, Ali Abdul Kadir
This paper examines security in Syria through the conceptual lens of the security gap, understood as the gap between security practices and objectives which have implications for individual and collective security. Practices of security can be the state apparatus, the military, and militias. The objective – safety – can refer to the safety or security of a range of collectives including the state, political parties, and ethnic groups, while individual security refers to the general safety of inhabitants and the protection of human rights. This paper compares the security situation in so-called 'rebel-held' areas of Syria where alternative governance structures have emerged, examining the security approaches of Local Administrative Councils and Rebel Councils in Deir Azzor, Manbij, Dera, and areas dominated by the Kurdish Democratic Union Party (PYD). It argues that security and safety are strongly influenced by authority formation and the nature of deals and relationships involved in the formation of these nascent authorities. It also argues that security in these areas is strongly influenced by the Syrian government, which disrupts collectives that threaten its own collective security while giving limited support to those which serve its agenda of retaining power. It also demonstrates the limited utility of the 'regime' vs. 'rebel-held' dichotomy, as rebel groups at times must accommodate the Syrian state in limited ways for instrumental purposes. The article is based on fieldwork conducted in Turkey in 2013–2014, interviews conducted in 2015, and secondary sources based on field research.